Leveraging Social Media for Tourism Growth: A Case Study ff Edelweiss Wonokitri Village - Yudhistya Ayu Kusumawati; Wina Permana Sari; Lasmy Lasmy (Institut Bisnis dan Teknologi Indonesia, 2025)
This research investigates the potential of social media platforms to enhance tourism growth in Edelweiss Wonokitri Village. By analyzing current social media trends and best practices, this study aims to develop a comprehensive social media strategy tailored to the unique characteristics of the village. The research will explore the effectiveness of various social media platforms in reaching target audiences, generating interest, and driving bookings. Furthermore, it will examine the role of user-generated content, influencer marketing, and paid advertising campaigns in promoting tourism in Edelweiss Wonokitri. The findings of this research will provide valuable insights for tourism stakeholders in Edelweiss Wonokitri to effectively leverage social media for sustainable tourism development and community empowerment.